Vision of Peru according to Inca Garcilaso - de la Puente Candamo, José Agustín (Mercurio Peruano, 2016)
It is interesting to prove that after 400 years of the first edition of the Royal Commentaries, this is a book that is still read, bought in bookstores and requested in libraries. This is the greatest compliment that can be done: the credibility of a book, because this book is not sold on the corner of a traffic lights and is valid for one month but a book of permanent presence of Peru. Here is a fundamental idea that can not be reduced to a topic without content. It should lead to reflection on the national history, as Garcilaso is somehow the connecting thread of the Peruvian memory.